CCR6 as a possible therapeutic target in psoriasis - Hedrick, Michael N.; Lonsdorf, Anke Susanne; Hwang, Sam T.; Farber, Joshua M. (Expert opinion on therapeutic targets, 2010)
Importance of the field: Psoriasis is a common, chronic autoimmune disease of the skin. Despite a number of effective treatments, new therapies are needed with enhanced efficacy, safety and convenience. Chemokine receptors are GPCRs that control leukocyte trafficking, and like other GPCRs, are good potential drug targets. The chemokine receptor CCR6 is expressed on the TH17 subset of CD4+ T cells, which produces IL-17A/F, IL-22, TNF-α and other cytokines, and which has been implicated in the pathogenesis of psoriasis. CCR6 and its ligand, CCL20/MIP-3α, are highly expressed in psoriatic skin and CCR6 is necessary for the pathology induced in a mouse model of psoriasis-like inflammation.Areas covered in this review: This review summarizes the evidence for the importance of the IL-23/TH17 axis, and in particular CCR6 and CCL20 in psoriasis, dating from 2000 to the present, and discusses the possibility of inhibiting CCR6 as a treatment for the disease.What the reader will gain: The review informs the reader of the current thinking on the mechanisms of inflammation in psoriasis and the possible roles for CCR6 (and CCL20) in disease pathogenesis.Take home message: We conclude that CCR6 should be investigated as a potential therapeutic target in psoriasis.